A scoping study of paediatric continence service provision in the Great Southern region of Western Australia - Goetze, E.; McLean, K.; Thompsom, J.; Jacques, Angela; Briffa, K. (2016)
The aim in conducting this cross-sectional study was to survey 100 parents of children in pre-primary and year one in the Great Southern region of Western Australia to determine the number of children with urinary incontinence and, of those, how many were receiving treatment. The severity and associated risk factors were also investigated. Permission was sought from schools to recruit parents of children starting primary school to complete an online survey. Social media was used to enhance response rates. The response rate was 100/1665 (6%) of the total target population, 100/925 (10.8%) of children from participating schools. Overall, 40% of responders reported daytime urinary incontinence. Of the children with daytime urinary incontinence, 26.3% experienced mild and 73.7% moderate-severe daytime urinary incontinence. No child was reported to have severe daytime urinary incontinence. Nocturnal enuresis was reported in 46.9% of those who responded and 89.8% of children su.ered from at least one other lower urinary tract symptom. This study is significant as there are limited treatment options in regional Australia for paediatric daytime urinary incontinence. Only 23.7% of parents had sought medical treatment for their a.ected child. Further research is required to determine whether lack of parental awareness regarding the significance of incontinence and the availability of treatment services; or the lack of accessible services in regional and rural Australia is behind inadequate intervention for this condition. Larger sample sizes are required to accurately determine prevalence and to examine risk factors for daytime urinary incontinence in children.